Impulsivity and aggression in female BPD and ADHD patients: association with ACC glutamate and GABA concentrations - Ende, Gabriele; Bohus, Martin; Sobanski, Esther; Schmahl, Christian (Neuropsychopharmacology, 2016)
Borderline personality disorder (BPD) and attention-deficit-hyperactivity disorder (ADHD) are both characterized by high impulsivity and difficulties in controlling anger and aggression. In BPD, comorbid ADHD may further increase impulsivity. For both disorders, altered MR spectroscopy levels of the neurotransmitters glutamate and GABA as well as some correlations with impulsivity were previously reported. The objective of this study was to investigate the neurotransmitters glutamate and GABA in relation to impulsivity and aggression as expressed in the anterior cingulate cortex (ACC) in groups of female patients with BPD and ADHD, respectively. Associations of glutamate and GABA levels with further BPD (symptom severity) and ADHD aspects (hyperactivity and inattention) were exploratively evaluated. 1H MR spectra were acquired at 3T to determine glutamate to total creatine ratios (Glu/tCr) and GABA levels from the ACC in a BPD group (n=26), an ADHD group (n=22), and a healthy control (HC) group (n=30); all participants were females. Both patient groups showed higher scores on self-reported impulsivity, anger, and aggression compared with HCs. ACC GABA levels were significantly lower in ADHD than HC. Although measures of impulsivity were positively related to glutamate and negatively to GABA, for aggression only a negative correlation with GABA could be demonstrated. These data provide human in vivo evidence for the role of ACC Glu/tCr and GABA in impulsivity and aggression. If distinct associations of Glu/tCr and GABA for BPD and ADHD can be confirmed in future studies, this might yield implications for more specific pharmacological treatments.